(untitled) (Journal of Applied Learning and Teaching, 2022)
The purpose of this collective case study research was to discover the impact school culture, internal factors, and the state of flow have upon motivating a teacher to develop teaching expertise. This research was designed to determine why and how individual teachers can nurture their existing internal factors to increase their motivation to seek expertise development and to explore how school culture, internal factors, and state of flow may encourage or limit the development of expertise. One major finding of this study concerned how experts choose their professional learning experiences and build professional learning networks based on their perceived weaknesses in content, pedagogy, or social-emotional attributes. They seek to improve their weaknesses to improve student learning through the key motivating factor of Teacher-Student Kinship representing an almost family-like relationship. Expert teachers bond with peers within their school, but also bridge with peers outside of their school. This bonding and bridging have become more accessible with the use of various social media technological tools from YouTube to professional learning networks on Twitter. The use of social media and other technology tools has allowed experts to develop Professional Kinship and enhance their practice regardless of location and proximity with peers within their professional learning community. These major findings hold implications for theory, practice, and future research particularly in the realm of teacher quality and the change of mindset towards the profession and the standards of education.